2015
DOI: 10.1016/j.thromres.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic cell culture system for monitoring of sequential changes in endothelial cells after heat stress

Abstract: Endothelial damage induced by a highly elevated body temperature is crucial in some diseases including viral hemorrhagic fevers. Here, we report the heat-induced sequential changes of endothelial cells under shear stress, which were determined with a microfluidic culture system. Although live cell imaging showed only minor changes in the appearance of heat-treated cells, Hsp70 mRNA expression analysis demonstrated that the endothelial cells in channels of the system responded well to heat treatment. F-actin st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous studies evidenced changed in cell morphology upon moderate heating (from 38.7 to 42.5°C) and disruption of actin bundle filaments . In particular, heat‐stressed endothelial cells showed increased Hsp70 mRNA expression, which is mainly involved in partial refolding of damaged proteins, protein disposal and aggregation prevention . Higher temperatures could lead to Hsp70 exhaustion and accumulation of damaged proteins.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies evidenced changed in cell morphology upon moderate heating (from 38.7 to 42.5°C) and disruption of actin bundle filaments . In particular, heat‐stressed endothelial cells showed increased Hsp70 mRNA expression, which is mainly involved in partial refolding of damaged proteins, protein disposal and aggregation prevention . Higher temperatures could lead to Hsp70 exhaustion and accumulation of damaged proteins.…”
Section: Discussionmentioning
confidence: 94%
“…40 In particular, heat-stressed endothelial cells showed increased Hsp70 mRNA expression, which is mainly involved in partial refolding of damaged proteins, protein disposal and aggregation prevention. 41 Higher temperatures could lead to Hsp70 exhaustion and accumulation of damaged proteins. Studies on magnetic nanoparticles already showed their high heating capacity upon application of alternating magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Occludin expression is characteristic of the epithelial barrier function and is essential to enable valid permeability studies. The constant delivery of cell media to growing cells, coupled with the application of a constant shear stress has been shown to accelerate growth and differentiation compared to the standard Transwell static culture model that requires 21 days to achieve full differentiation. The application of the shear stress induces faster differentiation and promotes the formation of a confluent monolayer within 5 days. The dynamic conditions encountered in the IOAC microdevice replicate more closely those that exist within the human intestinal tract, which may account for these differences …”
Section: Resultsmentioning
confidence: 99%
“…This system may also be used for primary cell culture. 11 Primary cells require delicate culture conditions, and the PS substrate can be used with several coating reagents. Moreover, the temperature controller limits temperature fluctuations.…”
Section: Rf/6a 135 Vascular Endothelial Cell Culture In the Microchipmentioning
confidence: 99%
“…8 The microchip cell culture system enables continuous and rigorous flow control, which is advantageous in vascular biology studies. [9][10][11] Vascular dysfunction 12 is associated with major diseases such as diabetes and cancer, and microfluidic cell culture systems are excellent tools for elucidating the cellular mechanisms underlying these diseases. A microfluidic cell culture system has been developed as a perfusion system that mimics the in-vivo environment 13,14 and facilitates evaluation of shear stress.…”
Section: Introductionmentioning
confidence: 99%